2009
DOI: 10.1007/s00415-009-5132-4
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular-evoked myogenic potentials in vestibular migraine

Abstract: Sound-induced vestibular-evoked myogenic potentials (VEMPs) can be used to investigate saccular function, measured from the tonically contracted sternocleidomastoid muscles (SCM) in response to loud sound stimuli. The aim of the present study was to assess VEMPs in patients with vestibular migraine and to determine whether saccular function is affected by the disease. Furthermore, tests such as tilts of subjective visual vertical (SVV) and caloric testing were conducted to test whether deficits in the various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 45 publications
3
72
5
1
Order By: Relevance
“…Interestingly, in this population studied, the EcochG showed evidence of HE in a larger number of patients (10 of 16), than RM LEIM, suggesting that MRI may be less sensitive when compared to EcochG. In the study by Baier et al [8], myogenic potential evoked by the vestibule by sound induction (VEMP's) was performed in 63 patients, of whom 37 were women (mean age 42 years) and 26 men (mean age 50 years ), With definite MV diagnosis (26 patients) and probable MV (37 patients). They were classified according to the Neuhauser diagnostic criteria, with the intention of determining if the saccular function is altered or not by the disease.…”
Section: Resultsmentioning
confidence: 65%
“…Interestingly, in this population studied, the EcochG showed evidence of HE in a larger number of patients (10 of 16), than RM LEIM, suggesting that MRI may be less sensitive when compared to EcochG. In the study by Baier et al [8], myogenic potential evoked by the vestibule by sound induction (VEMP's) was performed in 63 patients, of whom 37 were women (mean age 42 years) and 26 men (mean age 50 years ), With definite MV diagnosis (26 patients) and probable MV (37 patients). They were classified according to the Neuhauser diagnostic criteria, with the intention of determining if the saccular function is altered or not by the disease.…”
Section: Resultsmentioning
confidence: 65%
“…Baier et al have reported 68 % reduced VEMP amplitude in 63 patients with vestibular migraine compared to controls. No difference was seen in the latencies and there was no correlation between VEMP amplitudes, tilts of subjective visual vertical (SVV) and caloric testing [21]. Hong et al have compared VEMP results in 30 patients with migrainous vertigo and 31 healthy volunteers and have found abnormal wave formation in the patient group.…”
Section: Discussionmentioning
confidence: 99%
“…This test is primarily used in otological disorders such as superior canal dehiscence syndrome, vestibular nerve disorders, acoustic tumor, benign paroximal positional vertigo, central vestibular disorders, Ménière's disease and hearing impairment (4)(5)(6)(7)(8)(11)(12)(13). In addition to those there have been a small number of studies with VEMP on neurological diseases affecting the brain stem such as multiple sclerosis, cerebrovascular diseases (brain stem involvement) and migraine (9,10,(14)(15)(16)(17)(18)(19)(20). In a VEMP study conducted on 20 basilar migraine patients by Lih-Jen et al, evoked potentials could not be recorded in 7 patients, two patients showed delayed responses bilaterally and one patient showed no response on one side and delayed response on the other.…”
Section: Discussionmentioning
confidence: 99%
“…Based on this finding, the researchers argued that inner ear structures including saccula may be affected in vestibular migraine in addition to brain stem pathology, and that this can lead to symptoms such as vertigo (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation